Significance of immune factors in Crohn's disease development - D. S. Stavtsev; T. A. Astrelina; O. V. Knyazev; T. V. Pukhlikova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyze modern approach to pathogenesis of Crohn's diseases (CD), to determine effect of individual immunogenetic factors on development and progression of disease, in particular, in relation to HLA profile.Summary. Series of the population studies, confirming association of HLA antigens with human diseases were carried out. Main histocompatibility complex (MHC) plays the leading role in immune response as well as in development of CD, therefore occurrence of disease is related to changes at genetic level. Many studies indicate relation of Crohn's disease to specific genes of HLA-system. Hence, scientists of USA, Canada, Spain, Finland confirmed association of HLA-DRB1*0103 allele with development of CD, as well as with course of inflammatory bowel diseases and their complications. Important role in development of Crohn's disease in different countries is played by specific groups of alleles. In Israel interrelation of CD with DR15, in Germany — with HLA-DRB1*0701, in China — with HLA-Cw*12, in Japan — with HLA-DRB1*0405 and 0410 was established. Associations with clinical forms of disease was found, in particular in Italy presence of DRB1*0304, DRB1*0305, DRB1*0307, DRB1*0309 is linked to total involvement of the large intestine, in Spain presence of HLA-DRB1*07 — with terminal ileitis at CD, HLA-DRB1*0103 — with colitis. It has been demonstrated, that certain HLA-haplotypes have stronger association with Crohn's disease. For example, in Japan presence of Cw*1202-B*5201-DRB1*1502 haplotype reduces the risk of CD development. In Russia these studies are less concerned and were carried out by serological HLA typing methods. So, development of Crohn's disease was associated with B14, DR3 and DR5.Conclusion. Presented ambiguous results are caused, first of all, by ethnic differences and different frequency of some alleles in different populations. Thus, assessment of predisposition and resistance to Crohn's disease requires detection of HLA-markers in each specific population group.